STUDY THE EFFECT OF PROCESS VARIABLE ON THE BENEFICIATION OF IRON ORE USING THE MAGNETIC CONCENTRATION METHOD: REVIEW - Fairuz Kalahari, Helmi
Iron is a metal that is widely used in human life. In general, iron is produced from its primary source, namely iron ore by the pyrometallurgical route. However, the presence of impurity minerals in iron ore can disrupt the process and reduce the quality of the iron produced. Therefore a beneficiation process is needed to increase iron content and reduce impurity mineral content in iron ore. One of the methods commonly used in the iron ore beneficiation process is magnetic concentration, because of the magnetic properties of iron ore and this method can be done wet or dry. Wet magnetic concentration is generally carried out using a wet high intensity magnetic separator or WHIMS and a wet low intensity magnetic separator or WLIMS. Meanwhile, dry magnetic concentration is generally carried out using a dry high intensity magnetic separator or DHIMS. However, each magnetic concentration method has its own limitations which affect the process of separating valuable minerals from impurities. This study aims to examine the process variables that exist in the beneficiation of iron ore by the magnetic concentration method and their effects on iron yield and iron content in the concentrate. This research begins with the collection of literature in the form of journals, articles, or books related to iron mineralogy, the theory of magnetism, and iron ore beneficiation by magnetic concentration. The literature that has been obtained is selected so that its content is in accordance with the research topic, then the process variable data from the literature is critically analyzed and conclusions are drawn. The process variables analyzed on the WHIMS tool were feed size, magnetic field intensity, wash water rate, and rotor rate. The process variables analyzed on the DHIMS device were the feed size, magnetic field intensity, feed rate, and rotor rate. Meanwhile, the process variables analyzed on the WLIMS tool were feed size, magnetic field intensity, rotor rate, and solids content. Furthermore, each conclusion is elaborated and compared with the theory from the literature review, so that new conclusions can be obtained that can answer the research objectives. The results showed that the increase in the size fraction of the feed will cause a decrease in the yield and concentration of concentrate, also there is a minimum feed size so that separation between minerals can occur properly. Iron gain will increase with increasing magnetic field intensity and decreasing rotor speed in both WHIMS, DHIMS, and WLIMS tools. In WHIMS, iron gain will increase with increasing wash water rate. In DHIMS, iron recovery will decrease as the feeding rate increases. At WLIMS, iron recovery decreases with increasing solids content.